1996
DOI: 10.1007/s004649910011
|View full text |Cite
|
Sign up to set email alerts
|

A double-blinded evaluation of intraperitoneal bupivacaine vs saline for the reduction of postoperative pain and nausea after laparoscopic cholecystectomy

Abstract: Intraperitoneal bupivacaine offered a detectable, albeit subtle benefit to patients undergoing LC. However, the effect was transient and had little impact upon the patient's convalescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
52
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(62 citation statements)
references
References 23 publications
9
52
0
1
Order By: Relevance
“…11,[23][24][25] Present study are consistent with Cunniffe MG et al who showed a significant decrease in shoulder tip pain after intraperitoneal bupivacaine using subdiaphragmatic administration of 80ml bupivacaine 0.125% plus epinephrine l/200,000 had no significant effect on total pain, parietal pain, visceral pain, or shoulder-tip pain as compared with saline. 26 Zmora and Elfberg demonstrate postoperative pain reduction with intraperitoneal bupivacaine after laparoscopic cholecystectomy, while Cunniffe have noted only reduced shoulder pain with overall pain not affected.…”
Section: Rt Shoulder Painsupporting
confidence: 88%
“…11,[23][24][25] Present study are consistent with Cunniffe MG et al who showed a significant decrease in shoulder tip pain after intraperitoneal bupivacaine using subdiaphragmatic administration of 80ml bupivacaine 0.125% plus epinephrine l/200,000 had no significant effect on total pain, parietal pain, visceral pain, or shoulder-tip pain as compared with saline. 26 Zmora and Elfberg demonstrate postoperative pain reduction with intraperitoneal bupivacaine after laparoscopic cholecystectomy, while Cunniffe have noted only reduced shoulder pain with overall pain not affected.…”
Section: Rt Shoulder Painsupporting
confidence: 88%
“…However, pain also plays a major role in the metabolic and endocrine response, and is instrumental in the impairment of postoperative pulmonary function. Various methods have been investigated for reducing postoperative pain, such as local anesthesia [15] , intraperitoneal infiltration of local anesthesia [16] , preoperative administration of anti-inflammatory drugs [17] , utilizing CO2 at body temperature, applying intrapleural morphine [18] , and combined use of NSAIDs and opioids [19] . Our findings indicated that infiltrating ropivacaine after surger y through the port site reduced pain intensity, the number of patients requiring postoperative analgesics, and hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…[7,8] Local anesthetic infiltration is often used to improve pain relief after laparoscopic cholecystectomy. [5,[9][10][11][12][13] The postoperative analgesic effect of intraperitoneal administration of local anesthesia after laparoscopic gynecologic surgery has proved to be effective and safe but there is lack of consensus regarding the dose, concentration, site, and manner of administration. [14][15][16][17][18] But the effect of the same procedure during laparoscopic cholecystectomy is controversial, and the reported results range from considerable pain reduction to no significant pain reduction.…”
mentioning
confidence: 99%